Assessing Police Stops of Pedestrians: Toward a New Generation of Benchmarks. Issue 4 (July 2022) - Smith, Michael R.; Tillyer, Rob; Smith, Mitchell; Lloyd, Caleb D.
This paper extends the stop and frisk literature from New York City by examining pedestrian stops made by San Jose, California, police officers from January 2013 through March 2016 with a particular focus on benchmarking. Using violent crime suspects and nuisance-related calls for service (CFS) as comparators, we consider whether San Jose Police Department (SJPD) officers disproportionately stopped individuals from the city's dominant racial and ethnic groups citywide and in certain police beats with high levels of nuisance calls. Using violent crime suspects citywide as a benchmark, Whites were significantly overrepresented among those stopped by the police while Hispanics, Asians, and Blacks were underrepresented. The CFS findings at the beat level were consistent with the citywide findings for Blacks but reversed direction for Hispanics and varied for Asians depending upon beat and call type. We discuss possible reasons for this divergence across benchmarks and racial/ethnic groups and consider the implications for future research.